Integrating Autocratic Leadership and TikTok-Ads Manager Analytics: A Mixed-Methods Study on Corporate Branding Enhancement - Ardiansyah, M Firmanda; Munif, Achmad; Janah, Sidanatul (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2026)
This study investigates how the interaction between autocratic leadership and TikTok Ads Manager shapes corporate branding outcomes and practitioner perceptions. Existing branding and leadership literatures treat authority structures and platform technologies as analytically separate, thereby overlooking their joint role in coordinating strategic control and algorithmic execution within digital campaigns. Using a mixed-methods design, the analysis combines campaign data and practitioner interviews to demonstrate that autocratic leadership structures decision clarity and message discipline, while TikTok Ads Manager operationalizes reach, allocation efficiency, and real-time adaptation. This interaction constitutes a governance–technology nexus that produces measurable gains in brand coherence and reputation rather than isolated performance effects. The implication is that firms must align leadership authority with platform capabilities to sustain consistent and adaptive branding under conditions of digital competition.